2023
DOI: 10.1063/5.0152667
|View full text |Cite
|
Sign up to set email alerts
|

Control of mush complex viscosity on mid-ocean ridge topography: A fluid–structure model analysis

Abstract: This article exploits the interaction dynamics of the elastic oceanic crust with the underlying mush complexes (MC) to constrain the axial topography of mid-ocean ridges (MORs). The effective viscosity (μeff) of MC beneath MORs is recognized as the crucial factor in modulating their axial high vs flat topography. Based on a two-step viscosity calculation (suspension and solid-melt mixture rheology), we provide a theoretical estimate of μeff as a function of melt suspension characteristics (crystal content, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Several studies reported the emplacement of mafic dikes in mushy regions beneath mid‐ocean ridges. Theoretical estimates suggest the mush viscosities in the order of 10 14 –10 16 Pa s (Mandal et al., 2018; Mckenzie, 1984; Sen et al., 2023), whereas crystal‐rich magma viscosities are as high as 10 10 Pa s (Mavko & Nur, 1975; Schmiedel et al., 2021; Takeuchi, 2004, 2011). In such magmatic environments, the viscosity ratio η * can be low enough (∼10 5 ), favoring the dike emplacement by purely instability mechanism, as observed in the USTG‐oil experiments (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported the emplacement of mafic dikes in mushy regions beneath mid‐ocean ridges. Theoretical estimates suggest the mush viscosities in the order of 10 14 –10 16 Pa s (Mandal et al., 2018; Mckenzie, 1984; Sen et al., 2023), whereas crystal‐rich magma viscosities are as high as 10 10 Pa s (Mavko & Nur, 1975; Schmiedel et al., 2021; Takeuchi, 2004, 2011). In such magmatic environments, the viscosity ratio η * can be low enough (∼10 5 ), favoring the dike emplacement by purely instability mechanism, as observed in the USTG‐oil experiments (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“… Natural values: (Arachchige et al., 2022; Galland et al., 2014; Gerbi et al., 2004; Head et al., 2021; Mandal et al., 2018; Poppe et al., 2019; Sen et al., 2023; S. Takeuchi & Nakamura, 2001; Wang et al., 2021). …”
Section: Laboratory Experimentsmentioning
confidence: 99%
See 1 more Smart Citation